2021
DOI: 10.1038/s41598-021-88886-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of aprotinin on influenza A and B viruses in vitro and in vivo

Abstract: Influenza viruses cause significant morbidity and mortality worldwide. Long-term or frequent use of approved anti-influenza agents has resulted in drug-resistant strains, thereby necessitating the discovery of new drugs. In this study, we found aprotinin, a serine protease inhibitor, as an anti-influenza candidate through screening of compound libraries. Aprotinin has been previously reported to show inhibitory effects on a few influenza A virus (IAV) subtypes (e.g., seasonal H1N1 and H3N2). However, because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Many peptides currently analyzed for their anti-SARS-CoV-2 effect are repurposing peptides. For example, aprotinin is a very long peptide (58 amino acid residues) already well-known as a transmembrane serine protease 2 (TMPRSS2) inhibitor influencing negatively influenza A and B viruses [ 51 , 52 ] replication. Several antimicrobial peptides (AMPs) have also been tested for their anti-SARS-CoV-2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many peptides currently analyzed for their anti-SARS-CoV-2 effect are repurposing peptides. For example, aprotinin is a very long peptide (58 amino acid residues) already well-known as a transmembrane serine protease 2 (TMPRSS2) inhibitor influencing negatively influenza A and B viruses [ 51 , 52 ] replication. Several antimicrobial peptides (AMPs) have also been tested for their anti-SARS-CoV-2 activity.…”
Section: Discussionmentioning
confidence: 99%
“… Drug Host Factor Mechanism Viruses Ref. Fludase (DAS181) SA Cleaves SA on the cell surface of host to prevent viral entry IV, PIV Zenilman et al (2015) Maraviroc (MVC) CCR5 A CCR5-antagonist, binds to CCR5 and blocks viral entry HIV-1 Woollard and Kanmogne (2015) Myrcludex B NTCP Binds to NTCP to block the viral entry into liver cells HBV, HDV Bogomolov et al (2016) Ezetimibe NPC1L1 Blocks viral entry by binding to NPC1L1 HCV ( Feld et al, 2020 ; Monrroy et al, 2017 ) Aprotinin Endosomes A serine protease inhibitor, inhibition of viral protease activity during viral entry and endosome fusion IAV, IBV, SARS-CoV-2 ( Bojkova et al, 2020a ; Song et al, 2021b ) Niclosamide Endsomes A category B anthelmintic drug approved by FDA, targets acidic vacuoles, endosomes and interferes with membrane fusions. Also inhibits viral RNA replication and viral maturation SARS-CoV-2 DENV ( Backer et al, 2021 ; Jung et al, 2019 ) Emetine Lysosomes FDA approved drug for amebiasis, accumulates into the lysosomes, alters the pH to impair the intracellular traffic and inhibits autophagy to hinder the autophagy mediated viral infection, accumulation of emetine in lysosomes also limits free cholesterol availability for viral assembly ZIKV, EBV Yang et al (2018) Selective Inhibitor of Nuclear Export (SINE) Compound Verdinexor (KPT-185) Nuclear export A slow-reversible inhibitor of Exportin 1(CRM1/XPO1), inhibits interaction between NEP and exportin-1 (XPO1) to prevent nuclear export in vRNP.…”
Section: Hdts In Viral Diseasesmentioning
confidence: 99%
“…In addition to cell surface receptors, viruses also depend on host proteases for their surface protein splicing which aid them in host entry ( Böttcher-Friebertshäuser et al, 2013 ; Izaguirre, 2019 ). Aprotinin, a serine protease inhibitor which is in clinical use in Russia prevents influenza virus membrane fusion ( Song et al, 2021a ; Zhirnov et al, 2011 ). The effectiveness of aprotinin against SARS-CoV-2 has also been demonstrated at therapeutically achievable concentrations ( Bojkova et al, 2020a ).…”
Section: Development Of Novel Hdts Against Broad Range Of Viral Diseases Including Unknown Viral Pathogensmentioning
confidence: 99%
“…APR inhibits transmembrane serine protease 2 (TMPRSS2), which is actively involved in the viral entry process [ 12 , 24 , 25 , 26 , 27 , 28 , 29 ], and also the cleavage of hemagglutinin (HA), which is required for influenza virus fusion with a host cell and which can also be facilitated by TMPRSS2 during viral egress and by the membrane-bound human airway-trypsin like protease (HAT) prior to attachment to host cells [ 19 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that APR inhibits a broad spectrum of influenza A viruses (IAV) and influenza B viruses (IBV). Anti-influenza viral activity includes seasonal human IAVs (H1N1 and H3N2 subtypes): A/CA/04/09 (H1N1) [ 34 ], A/PR/8/34 (H1N1) [ 18 , 35 , 36 ], A/WSN/34 (H1N1) [ 37 ], A/CA/04/09 (pH1N1), A/Hamburg/05/2009 (pH1N1) [ 36 ], A/Aichi/2/68 (H3N2) [ 18 , 35 , 37 ], and A/PH/2/82 (H3N2) [ 35 ]; avian IAVs A/AB/Kor/CN2/09 (H5N2), A/AB/Kor/CN05/09 (H6N5) and A/Ck/Kor/01310/01 (H9N2) [ 35 ]; an oseltamivir-resistant IAV: A/Bris/10/07 H3N2 [ 37 ]; IBV B/Seoul/32/2011 [ 35 ], B/Hong Kong/73 [ 30 ], and B/Lee/40 [ 30 ]. It should be noted that the aprotinin-based aerosol patented in 2010 for the treatment of viral respiratory infections [ 38 ] has been approved in Russia for the treatment of influenza [ 19 ].…”
Section: Introductionmentioning
confidence: 99%